(untitled) (Research, Society and Development, 2021)
Objective: to understand the academic perception of active methodologies through the experience of creating video classes through Project Based Learning. Methodology: qualitative, observational, experience report developed in a debate with students from a University in Belém / PA. The experience was carried out by the students of the Physiotherapy Course, during the course of Biophysics, in the month of May 2018. A meeting was held with students and teachers of the Institution at the time of class administration, emphasizing Project-Based Learning and the difficulties traditional methodology. Results: the main aspect highlighted in the experience was the students’ perception of active methodology through video lessons through the concepts of Excellent, Good, Regular, Bad or Very Bad. The Excellent concept was most chosen by the students, with more than 2/3 of the total students. Conclusion: the experience allowed a better understanding of the students’ perception of active methodologies, especially Project-Based Learning through video lessons. Therefore, further studies on the influence of Project Based Learning on student learning are essential.